Desenvolvimento territorial : arranjos institucionais e ações públicas efetivadas no território do litoral norte alagoano - Mendonça, Luciana Chagas Uchôa de (2019)
The purpose of this study was to analyze the existing relationships between institutional arrangements that act directly or indirectly in the social management of territorial development and public actions carried out in the North Coast of Alagoano, making a diagnosis about the intervention of these actions in the process of territorial development and evaluating in fact they have leverage the social and economic growth of the resident population in this area of the State of Alagoas, because it is an area with different climatic, economic and social conditions. The study began with a historical survey of the process followed by the systematization of the main phases of the decentralization process in the region, focusing on the experience of the Territorial Collegiate work as an arrangement with strong decision-making power and a search for public policies. An analysis was made of existing institutional arrangements as well as their levels of action and public actions implemented through the Citizenship Territories Program, as well as evaluating the effectiveness of state action and the issue of social participation in planning, implementing and monitoring development of the region. Initially a bibliographic review was done on the subject besides the documentary analysis and open and semi-structured interviews. As a result of the research, it was intended to contribute with reflections to streamline and qualify the existing processes of application of public resources through the actions already implemented by the public actors involved with the Territory. It urges to emphasize that the complexity of the Citizenship Territories Program, initially planned and formatted by the Federal Government, but whose execution was carried out by the local authorities, ended up highlighting the social conflicts in the field and the collapse of the existing groups in the composition of the Collegiate as well as the relations of power and the political position of the State in the Territory. Finally, it is noted that the Territory had a large contribution of resources via PTC, and not all actions were done through the Collegiate, but that should be analyzed in the same way, because the number of actions that could have been implemented through cohesive social management is considerably important for analytical reflection.